Strategies for Development of Tourism Industry in Nepal: A Case Study of Pokhara Valley - Raj Adhikari, Shukra (MVIC Journal of Management and Information Technology, 2025)
This research explores the development strategies of Nepal’s tourism industry, with a particular focus on the Pokhara Valley. Considering tourism’s vital contribution to Nepal’s economy, the study emphasizes evaluating service quality, tourist satisfaction, and stakeholder involvement. The scope centers on key aspects such as the satisfaction levels of foreign tourists, challenges in tourism service delivery, and the roles of both government and the private sector in promoting tourism. Adopting a descriptive research design, the study surveyed 200 respondents, including foreign tourists, hotel owners, travel agents, and government officials, using multiple-choice and Likert-scale questionnaires. Collected data were analyzed descriptively to assess trends, perceptions, and stakeholder viewpoints on tourism development. The findings reveal that while overall tourist satisfaction is high, challenges persist in areas such as infrastructure, service quality, and policy implementation. Tourists particularly appreciate Pokhara’s natural beauty and hospitality but express concerns regarding transportation, pricing, and limited governmental support. The study concludes that strengthening infrastructure, revising policies, and enhancing private sector participation are crucial for sustainable tourism growth. For policymakers, these findings offer valuable insights into addressing current challenges and leveraging innovation to advance Nepal’s tourism sector.